2020
DOI: 10.1016/j.foodres.2020.108979
|View full text |Cite
|
Sign up to set email alerts
|

β-lactoglobulin micro- and nanostructures as bioactive compounds vehicle: In vitro studies

Abstract: Lactoglobulin (β-Lg) is known to be capable to bind hydrophilic and hydrophobic bioactive compounds. This research aimed to assess the in vitro performance of β-Lg micro-(diameter ranging from 200 to 300 nm) and nano (diameter < 100 nm) structures associated to hydrophilic and hydrophobic model compounds on Caco-2 cells and under simulated gastrointestinal (GI) conditions. Riboflavin and quercetin were studied as hydrophilic and hydrophobic model compounds, respectively. Cytotoxicity experiment was conducted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 68 publications
0
13
0
1
Order By: Relevance
“…Subsequently, at the end of the intestinal phase, it was observed that HD reached 100% for the protein concentrate (p ≤ 0.05). Most probably, the proteolytic enzymes present in the pancreatin completely digested the proteins from the concentrate into smaller peptides (Simões, Martins, et al, 2020). The full digestion of proteins facilitates its absorption into the bloodstream.…”
Section: In Vitro Protein Digestibility Testmentioning
confidence: 99%
“…Subsequently, at the end of the intestinal phase, it was observed that HD reached 100% for the protein concentrate (p ≤ 0.05). Most probably, the proteolytic enzymes present in the pancreatin completely digested the proteins from the concentrate into smaller peptides (Simões, Martins, et al, 2020). The full digestion of proteins facilitates its absorption into the bloodstream.…”
Section: In Vitro Protein Digestibility Testmentioning
confidence: 99%
“…Control cells were grown with complete medium. The cellular viability was assessed using the Thiazolyl Blue Tetrazolium Bromide (MTT) reduction assay according to Simões et al [20]. MTT produces a yellowish solution that is converted to dark blue, water-insoluble MTT formazan by mitochondrial dehydrogenases of living cells.…”
Section: Antiproliferative Activity In Colon Cancer Cell Linesmentioning
confidence: 99%
“…[54] After the bread samples passed from the oral to the gastric phase, the hydrolyzed starch remained similar, with no statistically significant differences between both phases (p >0.05). Conditions during the gastric phase were simulated to human physiological conditions, gastric conditions were similar to those described by Simões et al, [55] they were characterized by high ionic strength (values around 100 mmol L -1 ) and acidity (a pH value of 3) and these conditions inhibit the action of 𝛼-amylase and the hydrolysis of the starch was interrupted. In human digestion, the change in pH is gradual and enzymatic work continues, so that starch digestion continues even during the gastric phase, [54] in the protocol carried out for the simulation of digestion, the change in pH was immediate, so the digestion of the starch was interrupted during this phase.…”
Section: In Vitro Digestion Of Starch and Determination Of Nutritionally Important Starch Fractionsmentioning
confidence: 99%